Association between amino acids and recent osteoporotic fracture: a matched incident case-control study - Liang, Bing; Shi, Xinyan; Wang, Xinwei; Ma, Chao; Leslie, William D.; Lix, Lisa M.; Shi, Xianbao; Kan, Bo; Yang, Shuman (Frontiers in Nutrition, 2024)
Context Osteoporotic fracture is a major public health issue globally. Human research on the association between amino acids (AAs) and fracture is still lacking. Objective To examine the association between AAs and recent osteoporotic fractures. Methods This age and sex matched incident case-control study identified 44 recent x-ray confirmed fracture cases in the Second Hospital of Jilin University and 88 community-based healthy controls aged 50+ years. Plasma AAs were measured by high performance liquid chromatography coupled with mass spectrometry. After adjusting for covariates (i.e., body mass index, milk intake > 1 time/weekfrequency, falls and physical activity), we conducted conditional logistical regression models to test the association between AAs and fracture. Results Amongst cases there were 23 (52.3%) hip fractures and 21 (47.7%) non-hip fractures. Total, essential, and non-essential AAs were significantly lower in cases than in controls. In the multivariable conditional logistic regression models, after adjusting for covariates, each standard deviation increase in the total (odds ratio [OR]: 0.304; 95% confidence interval [CI]: 0.117-0.794), essential (OR: 0.408; 95% CI: 0.181-0.923) and non-essential AAs (OR: 0.290; 95%CI: 0.107-0.782) was negatively associated with recent fracture. These inverse associations were comparable mainly found for hip fracture, rather thanand non-hip fractures. Among these AAs, lysine, alanine, arginine, glutamine, histidine and piperamide showed the significantly negative associations with fracture. Conclusions There was a negative relationship between AAs and recent osteoporotic fracture; such relationship appeared to be more obvious for hip fracture.